Terahertz Wave Propagation Characteristics in Graded Teflon Based Solid-Core Photonic Crystal Fibre. Issue 1 (1st February 2023) - Dash, Shikhar; Mathur, Varun; Pandey, Nilesh; Sinha, Ravindra K.
Abstract: In the past few years, photonic crystal fibre (PCF) in the Terahertz spectrum is drawing significant attention because of its multifaceted applications in high-speed data communication, spectroscopy, sensing, etc. The proposed PCF structure is based on a Teflon solid core surrounded by porous cladding. Teflon has been used as a background material because of its high flexibility and the possibility of making longer PCFs, which is capable of guiding waves in the THz region. The porous cladding consists of circular air-holes positioned hexagonally whose diameters increase with each subsequent layer keeping the pitch constant thus providing a graded-index profile. The diameters of air holes in each hexagonal layer are 1 mm, 1.2 mm and 1.5 mm respectively, maintaining a constant pitch of 2mm and a perfectly matched layer (PML) thickness of 3mm. We have examined the transmission characteristics of the proposed profile in the frequency range of 0.8 THz to 2.5 THz. The modal solution of the profile is solved using the Finite Element Method based on COMSOL Multiphysics version 5.5. Using the graded-index profile, we have obtained a large effective modal area of around 5.6 mm 2 at 1 THz and a low confinement loss of 2.25 × 10 −4 dB/km at the same frequency. Due to this large effective modal area, we get higher damage threshold and weaker non-linear effects, making it suitable for high power applications.